ISOLASI ACTINOMYCETES SIMBION SPONGE PULAU BARRANG CADDI MAKASSAR SEBAGAI PENGHASIL SENYAWA ANTIMIKROBA - Herlina - Rante; Gemini Alam; Usmar Usmar; Sri Ningrum Anggrainy Anggrainy Wahid (Majalah Farmasi dan Farmakologi, 2020)
Sponges as a residence for microorganisms make it a High Microbial Abundance Sponge (HMAS) where 40-60% of the biomass of the sponge consists of microorganisms. One of the bacteria that originates from the sea and has long been known to be breed is Actinomycetes. Actinomycetes that are symbiotic with sponges are very numerous and rich in the discovery of new chemotypes with interesting therapeutic activities that are not found in terrestrial organisms. The purpose of this study was to determine the antimicrobial activity of Actinomycetes isolates obtained from Barrang Caddi Island sponges. Actinomycetes isolation was carried out by pour and spread plate methods. From seven  isolates actinomycetes obtained from sponge collections from Barrang Caddi Island,  Makassar City, South Sulawesi are able to inhibit test microbes in initial screening with antagonistic test.